أفعال الصّلاة وآثارها الإيجابيّة - عبد الله سليمان, عمر إسماعيل (Gezira Journal of Educational Sciences and Humanities, 2026)
قضت حكمة الله ورحمته بخلقه - لعلمه بما يصلحهم - أن ربطهم بأمور تكسبهم قوًة تعينهم على تحمل مشاق الحياة، بالرًغم من اتًصافهم بالضعف، ومن هذه الأمور الًتي تكسب الإنسان القوًة البدنيًة والروحيًة وتورث السًكينة والطًمأنينة: الصًلاة، وإذ جعل الله الصًلاة أقرب الصلات إليه، فلا ريب أن جعل فيها من المنافع ما يستحق أن يلتزمها كل مخلوق عاقل، لذا هدفت هذه الدراسة إلى تسليط الضوء بقدر الإمكان على التًالي: الكشف عن بعض فوائد الصًلاة البدنيًة والروحيًة، بالوقوف على ما في أفعال الصًلاة من تأثير إيجابي واضح على جميع أعضاء الجسم، استجلاء ما اشتملت عليه الصًلاة من حركات متنوعة تعمل بشكل فعال على وقاية أعضاء الجسم من كثير من الأمراض التي تشكو منها كثير من المجتمعات، لفت الأنظار والعقول إلى ما تحمله فريضة الصّلاة من منافع روحيًة ومادية في الوقاية والاستشفاء من كثير من أمراض عضويًة ونفسية، مستشفةً من دلالات كثير من النًصوص، وأخرى تكشّفت عن الممارسة والملاحظة والتًجربة. اتًبعت الدراسة المنهج الاستقرائي والوصفي، توصّلت الدراسة إلى أنّ تشريع الله للصًلاة فيه سر لطيف؛ نظراً لكونها شرعت على الأمم لتحقّق مقاصد كثيرة زائدة على التعّبد، وإن جهلها النًاس على مر التًاريخ، وأنً من منافع الصلاة ما يقي ويعالج عللاً كان من الممكن أن تفتك بالبشرية، وأنّ عدم إسقاطها عن المكلّف وهو في أحلك الظروف يشي بشكل جليّ أهمّيتها في حياة الإنسان، وأنّ الصّلاة بتلك المنافع تحمل من الإعجاز ما يدهش العقول التي هي قمةً في التًنوير. أوصت الدراسة بضرورة دراسة الشّعائر التّعبّديّة وبيان حكمها وما تتضمّنه من منافع وفوائد؛ إبرازاً لعلم الله اللامتناهي في الدقة، وحكمته البالغة، ورحمته الواسعة بعباده في كل ما شرع وقضى، كما أوصت بتسليط الضّوء على أهمّيّة شعيرة الصّلاة روحياً وبدنياً، وضرورة أدائها على المنهج النّبويّ، وتنشئة النّشء عليها لتحقيق الثّمرة المرجوّة من إقامتها. وأوصت بإجراء دراسات مقاصدية لبيان أسرار التشريعات الرّبّانيّة وغاياتها وثمارها الدّنيويّة والأخوية. The wisdom of Allah and His mercy to His creation, due to His foreknowledge of what is best for them, He has linked them to things that assist them to endure the hardship of life, despite their weakness. Some of these things which acquire man physical and spiritual strength, and provide serenity and assurance: performance of prayers; thus Allah has made prayers the closest connection to Him. Therefore, undoubtedly He has made benefits that deserve to be committed to by every sensible creature. So, this study aims to shed as much light as possible on the following: uncovering some of the corporal and spiritual benefits of prayers, by mentioning the clear positive effect on all the parts of body; explicating what prayers contain from variants motions which eventually work to immune the organs of the body from many diseases that many communities complain of; drawing the attention of sights and minds to what prayers bear of spiritual and material benefits in preventing and treatment of so many physical and psychological diseases, deducted from the denotations of many texts, and others are clarified by practice, observation and experiment. The study has followed the descriptive deductive approach. The study comes to the conclusion that posing the prayers has an invisible secret, as they have been posed upon the nations to fulfill many purposes other than worshipping, even if they were unknown to people throughout history; persistence of performing to the committed in the bitterest circumstances explicitly shows their importance in human life; and that prayers with these benefits bear inimitability that puzzles the minds which are a peak in enlightening. The study recommends the necessity of following Allah's commandments and prohibitions in researches to explore the benefits they have for all mankind, to show out omniscience of Allah.